2019
DOI: 10.1038/s41372-019-0338-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of very low tidal volumes during high-frequency ventilation reduces ventilator lung injury

Abstract: The use of volume guarantee (VG) on high-frequency oscillatory ventilation (HFOV) allows to use fixed very low highfrequency tidal volume (VThf), maintaining adequate CO 2 removal while potentially reducing the risk of ventilator-induced lung injury. Objective To demonstrate that the use of very low VThf can be protective compared with standard VThf on HFOV combined with VG in a neonatal animal model. Study design Experimental study in 2-day-old piglets with induced respiratory distress syndrome ventilated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In this models, HFOV + VG with lower tidal volumes at frequencies as high as 20 Hz led to lower grades of inflammation and VILI compared to standard tidal volumes at 10 Hz after 12 h of mechanical ventilation. 10 T A B L E 2 Mean weight adjusted volumes and standard deviations (SD) for frequencies 13-20 Hz…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this models, HFOV + VG with lower tidal volumes at frequencies as high as 20 Hz led to lower grades of inflammation and VILI compared to standard tidal volumes at 10 Hz after 12 h of mechanical ventilation. 10 T A B L E 2 Mean weight adjusted volumes and standard deviations (SD) for frequencies 13-20 Hz…”
Section: Discussionmentioning
confidence: 99%
“…3,4 This strategy has proved to better maintain tidal volumes, partial pressure of CO 2 (pCO 2 ) and oxygen saturation, [5][6][7] and although evidence remains unclear, some studies have suggested that VG might lead to lower rates of death and BPD. 8,9 In experimental models, the protective effect of HFOV-VG has been proved when using smaller volumes and very high frequencies, 10 which have been successfully used in preterm newborns in a pilot study. 11 Despite the growing evidence that HFOV-VG could be an alternative for conventional mechanical ventilation in very immature newborns, there are few studies describing which volumes and frequencies lead to adequate ventilation and should initially be set.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in circuit volume might act as a mechanical low-pass filter and reduce the fluctuations. However, it should be considered that some degree of high-frequency oscillation could facilitate expulsion of bronchial secretions [8] and potentially, to some extent, exert the benefits of high-frequency ventilation [9, 10, 11].…”
Section: Discussionmentioning
confidence: 99%
“…BAL (30 ml/kg; 37°C with F iO2 : 1) was performed to induce SF‐deficient lung injury 20,21 . At the end of BAL procedure, positive pressure ventilation settings were F iO2 = 1.0 21–23 and PEEP = 5 cmH 2 O, and to avoid barotrauma, f R and PIP were adjusted to a maximum of 42 breaths/min and 25 cmH 2 O, to maintain V T = 8–10 ml/kg. Lavage procedures were repeated (every 5 min) until arterial blood partial pressure of oxygen (P aO2 ) <100 mmHg.…”
Section: Methodsmentioning
confidence: 99%